India in Indo-Pacific: Cooperation Dynamics and Way Forward - De, Prabir (AEI Insights, 2023)
India’s journey from Look East to Indo-Pacific has evolved under a multipolar world, where India has always dealt with global challenges in a cooperative manner. The ‘Indo– Pacific’ construct has gained significant attention globally and is advancing rapidly. It is a multipolar region, contributing more than half of the world’s GDP and population. This is, in fact, a region in which several world powers are getting engaged simultaneously, especially in geo-economic terms. Today, Indo-Pacific countries are becoming more economically integrated, with ample scope for further deepening this integration process. Enhancing regional integration in Indo-Pacific is a multifaceted task that will require the implementation of strong policy initiatives. This article briefly reviews India’s Indo-Pacific journey on the connectivity front, identifies challenges and presents a way forward.